2011
DOI: 10.5194/bg-8-703-2011
|View full text |Cite
|
Sign up to set email alerts
|

Carbon monoxide apparent quantum yields and photoproduction in the Tyne estuary

Abstract: Abstract. Carbon monoxide (CO) apparent quantum yields (AQYs) are reported for a suite of riverine, estuarine and sea water samples, spanning a range of coloured dissolved organic matter (CDOM) sources, diagenetic histories, and concentrations (absorption coefficients). CO AQYs were highest for high CDOM riverine samples and almost an order of magnitude lower for low CDOM coastal seawater samples. CO AQYs were between 47 and 80% lower at the mouth of the estuary than at its head. Whereas, a conservative mixing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 37 publications
5
56
2
Order By: Relevance
“…For example, in a salinity transect in the Delaware Estuary (from salinity 3 to 21), AQYs at 350 nm were remarkably constant, at about 1 × 10 −4 mol DIC (mol quanta) −1 (±~10% RSD), while corresponding CO AQYs decreased by a factor of about 1.6 with increasing salinity (from ~1.6 × 10 −5 mol CO (mol quanta) −1 to ~1.0 × 10 −5 mol CO (mol quanta) −1 ), suggesting that DIC and CO are formed by different photochemical mechanisms (White et al, 2010). A similar decrease in CO AQYs down a temperate estuary was observed by Stubbins et al (2011).…”
Section: Photochemical Dic Formation and Oxygen Consumption A Dic Phosupporting
confidence: 70%
“…For example, in a salinity transect in the Delaware Estuary (from salinity 3 to 21), AQYs at 350 nm were remarkably constant, at about 1 × 10 −4 mol DIC (mol quanta) −1 (±~10% RSD), while corresponding CO AQYs decreased by a factor of about 1.6 with increasing salinity (from ~1.6 × 10 −5 mol CO (mol quanta) −1 to ~1.0 × 10 −5 mol CO (mol quanta) −1 ), suggesting that DIC and CO are formed by different photochemical mechanisms (White et al, 2010). A similar decrease in CO AQYs down a temperate estuary was observed by Stubbins et al (2011).…”
Section: Photochemical Dic Formation and Oxygen Consumption A Dic Phosupporting
confidence: 70%
“…5). This is in contrast to other studies in the St. Lawrence River estuary (Zhang et al, 2006), the Beaufort Sea (Xie and Zafiriou, 2009) and the Tyne River estuary (Stubbins et al, 2011). These studies did not address CO 2 photochemistry, but all three found an increase in CO AQY values with increasing CDOM absorption coefficients using transect data from high absorption (upper estuary) to low absorption (coastal) waters.…”
Section: Water Sample Characteristics and Their Relationship To Photocontrasting
confidence: 53%
“…Each have shown a decrease in the photochemical efficiency of CO production with decreasing salinity. Stubbins et al (2011) also found an inverse trend between CO AQYs and salinity in the Tyne River estuary. This was not explained by simple conservative mixing and suggests that this relationship is more strongly tied to CDOM.…”
Section: Water Sample Characteristics and Their Relationship To Photomentioning
confidence: 80%
“…Ultrapure water (Milli-Q) provided a blank. Blank corrected absorbance spectra were corrected for offsets due to scattering and instrument drift by subtraction of the average absorbance between 700 and 800 nm (Stubbins et al, 2011). Data output from the spectrophotometer were in the form of dimensionless absorbance (i.e., optical density, OD) and were subsequently converted to the Napierian absorption coefficient, a (m −1 ) (Hu et al, 2002).…”
Section: Dissolved Organic Carbon Concentrationsmentioning
confidence: 99%